2005
DOI: 10.1002/cne.20736
|View full text |Cite
|
Sign up to set email alerts
|

Stereological study of postnatal development in the mouse utricular macula

Abstract: This study describes the morphometric changes taking place in the utricular macula of mice with ages in geometric progression from 1 to 512 days after birth. By using design-based stereological methods, the total volume and surface area of the sensory epithelium as well the total number of the hair cells and supporting cells were estimated. Finally, the numerical density, volume density, and mean volume of the individual cell types were determined. The major changes were found in the number of the individual c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 44 publications
3
33
0
Order By: Relevance
“…Those reports attributed the statistical increases to postnatal hair cell differentiation and the direct conversion of supporting cells into hair cells (Rusch et al 1998;Kirkegaard and Nyengaard 2005). However, we suspected that previously undetected populations of postnatally dividing progenitors might continue to produce progeny that would become new hair cells, thus contributing to the growth of the utricle's sensory epithelium.…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…Those reports attributed the statistical increases to postnatal hair cell differentiation and the direct conversion of supporting cells into hair cells (Rusch et al 1998;Kirkegaard and Nyengaard 2005). However, we suspected that previously undetected populations of postnatally dividing progenitors might continue to produce progeny that would become new hair cells, thus contributing to the growth of the utricle's sensory epithelium.…”
Section: Introductionmentioning
confidence: 78%
“…Interpretation of those limited data appeared to lead to the conclusion that little or no mitotic production of hair cells occurs in mice after birth (Rusch et al 1998;Kirkegaard and Nyengaard 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in Kir2.1 mRNA expression during the 1st postnatal wk also coincided with the continued maturation of the vestibular system in mice (Rüsch et al 1998). Furthermore, the total number of mature hair cells continues to increase until P16 (Kirkegaard and Nyengaard 2005;Li et al 2008), which may contribute to the higher Kir2.1 mRNA expression level measured at P25 compared with P7.…”
Section: Inward Rectifier Currents In Utricle Hair Cellsmentioning
confidence: 87%
“…None of the other Kir2 family subunits displayed substantial expression at the developmental onset of I K1 or at any time point that we examined. Furthermore, Kirkegaard and Nyengaard (2005) found that hair cell numbers in mouse vestibular epithelia increase until P16. A larger number of hair cells expressing Kir2.1 are consistent with our data, which show an increase in Kir2.1 mRNA expression between P7 and P25.…”
Section: Kir2mentioning
confidence: 99%